A holistic cyber security implementation framework. Issue 3 (2014) - Issa Atoum; Ahmed Otoom; Amer Abu Ali
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to propose a holistic cyber security implementation framework (HCS‐IF) that lays out the ground for a conceptual, coherent, systematic, overarching and consolidated approach to implement cyber security strategies (CSSs). Design/methodology/approach – The HCS‐IF is conceptually proposed to address the actual needs that are extracted from literature review. The HCS‐IF uses and integrates a set of high‐level conceptual security controls, solutions, processes, entities, tools, techniques or mechanisms that are already known in the domains of information security management, software engineering and project management to address the identified needs. Findings – The HCS‐IF components and controls collectively interact and cooperate to implement CSSs. The proposed framework is compared with other related frameworks, and the results show that the HCS‐IF outperforms other frameworks on most of the suggested comparison criteria. Originality/value – From a practical standpoint, governments and practitioners alike stand to gain from the findings of this research. Governments who want to implement CSSs on a national level will find the proposed framework useful in overseeing cyber security implementation. Practitioners will be prepared to address the anticipated cyber security implementation challenges and the required controls needed to facilitate cyber‐security implementation in a holistic overarching manner. <ack> <x xml:space="preserve"> Acknowledgements </x> The authors are grateful to Eng. Fahd A. Batayneh for his valuable comments and fruitful discussions. </ack>